The Role of Organ and Leaf Habit on the Secondary Xylem Anatomy Variation across 15 Species from Brazilian Cerrado - Dutra, Rafaella [UNESP]; Nogueira, Anselmo; Rossi, Sergio; Chacon Dória, Larissa; Buttò, Valentina; Marcati, Carmen Regina [UNESP] (MDPI, 2023)
Xylem is a complex tissue connecting the organs of plants and it performs multiple functions, including water transport, mechanical support, and storage. Because of the interaction between structure and function, xylem anatomy can provide useful information about its role in plant strategies. However, knowledge of how xylem anatomical traits change across organs and species functional groups is still limited. Here, we tested the role of different plant organs (stem and roots) and leaf habits (deciduous, semi-deciduous, and evergreen) on xylem anatomy variation across 15 woody species from the Brazilian Cerrado. Vessels, fibers, and parenchyma traits were measured on 45 individuals sampled in 2014 in Botucatu, São Paulo, Brazil. Our results revealed a higher parenchyma fraction and less fiber fraction in roots than in stems across species. Differences in wood anatomical traits between organs were mainly species-specific in parenchyma traits rather than vessel and fiber traits. Across leaf habits, only the root ray fraction was higher in evergreen species compared to deciduous species. These findings highlight a potential role of organs and leaf habits in xylem storage across Cerrado woody species.
Keywords: functional traits; neotropical savanna; ray parenchyma; wood allocation space; xylem plasticity